Answer:
The equation of the exponential function will be:
Explanation:
The general exponential function is defined as
y = abĖ£
Here,
- a is the initial value and b is the growth factor
From the table, it is clear that the y-intercept is (0, 10). Note that the y-intercept can be determined by setting x=0 and solving for y.
here
at x=0, y=10
so a = 10
If we check the y-values, it is clear that every next value of y can be obtained by multiplying the previous y-value by 1/5.
In other words, the common multiplier = b = 1/5
Thus, the equation becomes
Thus, the equation of the exponential function will be: